EFEKTIVITAS PEMBELAJARAN MENULIS TEKS IKLAN DENGAN MENGGUNAKAN METODE ACTIVE LEARNING PADA SISWA MTS - Cep Muhlisin; Eli Syarifah Aeni (IKIP Siliwangi, 2019)
As a student or teacher, writing cannot be separated. Writing means the process of expressing ideas through writing. So the more we write, it means that the more our thoughts are contained in writing. This research is motivated by the low value of writing ad text on junior high school students, this is evidenced by the results of interviews with Indonesian teachers who stated that advertising text material is new material that is in learning in junior high schools. Therefore, researchers formulate how the results before and after learning to write ad text using the active learning method in class VII students. The purpose of this study was to determine the success and effectiveness of active learning methods in learning to write ad text. Therefore, the learning method used by researchers is the active learning method. In this study, researchers took the title of the effectiveness of learning to write ad text using the active learning method. In this study, researchers used quantitative methods. The population in this study amounted to 25 students of class VIII. Based on the data obtained, the initial test results of the average student score of 42.76. As for the final test that has used a learning method, the average value of students is 75.32.